Rubber wastewater treatment using UV, ozone, and UV/ozone and its effluent potency for microalgae Spirulina platensis cultivation medium. Issue 1 (1st January 2020) - Hadiyanto, Hadiyanto; Christwardana, Marcelinus; Indah Pratiwi, Detian; Silviana, Silviana; Syarifudin, Muhammad; Khoironi, Adian
Abstract: In this study, three different advanced oxidation processes (AOPs), namely UV, ozone, and a combination of UV/ozone, were applied for rubber wastewater treatment. The kinetics of chemical oxygen demand (COD), total nitrogen and total phosphorous removal in the rubber wastewater treated with the AOPs were investigated. Moreover, the optimum exposure time to treat wastewater with the oxidizing agents (UV, ozone, and both) was revealed. Furthermore, the effluent after the treatment was completed was tested as a potential microalgae culture medium. The reaction rate constant was in a range of 3 × 10 −4 to 1.2 × 10 −3 s −1, which was higher than the results of the second-order kinetics. UV/ozone combination was the best method to treat the rubber wastewater due to its higher reaction rate constant. The results indicated that a decrease in the COD was observed, following a first-order reaction with a high determination coefficient (R 2 ) (0.936–0.984). The COD removal was 81.44% when the UV/ozone method was used, and the removal of total nitrogen and phosphorus was 69.62% and 25.53%, respectively. Next, Spirulina platensis was cultivated in 30% (v/v) of the effluent obtained from the best method. The results showed that the microalgal growth rate and ODmax were 0.67 and 0.3 day −1, respectively. This research showed that the nutrients in wastewater effluent could be used as food supplements for microalgae production, and therefore, reduce the production costs in large scale microalgae cultivation bioprocesses.